Ser homem ou ser humano: reflexões psicanalíticas a respeito da desconstrução do conceito de masculinidade - Servelhere, Guilherme Rosa (Universidade Federal de São Carlos, 2025)
This study aims to present reflections on the concepts of man and masculinity, seeking to highlight the issues involved in this context based on an analysis of the phenomenon on two different scales: the group and the subjective. In addition, it aims to propose a dismantling of the hegemonic and paradigmatic weight of these categories, showing their essential contradictions throughout history. To this end, it covers part of the psychoanalytic theoretical scope, emphasizing Freudian works that, in effect, allow for a detailed reading of the concepts analyzed. Finally, it reflects on the possible directions that the proposed discussion may take, with the aim of raising one of several paths that can be taken in this scenario.
Being a man or being human: psychoanalytic reflections on the deconstruction of the concept of masculinity
Keywords: Masculinidade; Homem; Psicanálise; Culpa; Cultura; Controle; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO; 5. Igualdade de Gênero